Study of resistance pattern of isolated micro-organisms towards commonly used anti-microbial agents in medical intensive care unit of a tertiary care teaching hospital - Biswas, Mansij; Rege, Nirmala N.; Karnik, Niteen D.; Nataraj, Gita (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The objective of the study was to find out different types of biological samples from admitted patients tested for culture and sensitivity (C&S), prevalence of different types of organisms isolated from those samples, and to analyze the resistance pattern of those isolated organisms against commonly used or tested anti-microbial agents (AMAs). Methods: Following institutional ethics committee approval and written informed consent, adult patients of both genders, receiving AMAs were enrolled from June 2014 to July 2015 and followed up daily till they were in medical intensive care unit (MICU). Demographic data, diagnosis, culture-sensitivity (antibiogram) and other investigation reports and treatment details were recorded. Descriptive statistical analysis of collected data was done. Results: Of the 514 samples (from 600 patients enrolled) sent for C&S testing, 143 were reported as sterile while from the rest 371 samples, 504 organisms were isolated; commonly isolated organisms were Pseudomonas aeruginosa (30%), Acinetobacter baumannii (23%), Klebsiella pneumoniae (16%), Providencia sp. (7.1%), Escherichia coli (5.7%), and Enterobacter sp. (4.2%). Samples were sent in 63% of enrolled patients, the commonest being broncho-alveolar lavage (48% of total). Microbial resistance was high for cephalosporins (ceftriaxone, cefepime, ceftazidime), carbapenems (meropenem, imipenem), penicillins (piperacillin), quinolones (ciprofloxacin, levofloxacin), aminoglycosides (gentamicin, netilmicin, amikacin) and cotrimoxazole. Most organisms were sensitive to colistin (100%), polymyxin B (92%) and tigecycline (69%). Conclusions: The information regarding commonly isolated organisms and their resistant pattern would aid in rational selection of AMAs and thus the present study is useful to clinicians managing MICU and the hospital infection committee to plan future policies regarding AMA use in MICU.